2006
DOI: 10.1007/s00436-005-0113-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of egg-propagated Eimeria tenella (local isolates) gametocytes as vaccine(s) against mixed species of coccidia in chickens

Abstract: Egg propagated gametocytes of Eimeria tenella (local isolates) were used to prepare the adjuvanted (Amphigen) and nonadjuvanted vaccine(s) and evaluated on the basis of cellular, humoral, and challenge responses. Modified splenic cell migration inhibition test and enzyme-linked immunosorbant assay were used to assess the cellular and humoral responses, respectively. Chicken in groups A, B, C, and D were given adjuvanted vaccine (orally), adjuvanted vaccine (subcutaneously, s/c), nonadjuvanted vaccine (orally),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…We [4]–[7] and others [8][10] have previously shown that immunization of breeding hens – either with purified gametocyte antigens or via deliberate infection with E. maxima – results in the passive maternal transfer of large quantities of anti-parasite IgG from hen to egg yolk and, hence, to young chicks, protecting those chicks against infection. In laboratory-controlled conditions, the level of protection is very high, with complete abrogation of oocyst shedding being observable [5]–[7].…”
Section: Introductionmentioning
confidence: 99%
“…We [4]–[7] and others [8][10] have previously shown that immunization of breeding hens – either with purified gametocyte antigens or via deliberate infection with E. maxima – results in the passive maternal transfer of large quantities of anti-parasite IgG from hen to egg yolk and, hence, to young chicks, protecting those chicks against infection. In laboratory-controlled conditions, the level of protection is very high, with complete abrogation of oocyst shedding being observable [5]–[7].…”
Section: Introductionmentioning
confidence: 99%
“…The inoculation of sporozoites (1.0 × 10 4 ) into 10- day-old chicken embryos resulted in a mortality rate of only around 10%, much lower than the reported rate of 86.4 % (Hafeez, Akhtar and Ayaz, 2006, 2006, 2007). However, mortality was higher in younger embryos or those given a higher dose of sporozoites.…”
Section: Discussionmentioning
confidence: 63%